The Impact of Tregs on the Anticancer Immunity and the Efficacy of Immune Checkpoint Inhibitor Therapies - González-Navajas, Jose M.; Fan, Dengxia Denise; Yang, Shuang; Yang, Fengyuan Mandy; Lozano-Ruiz, Beatriz; Shen, Liya; Lee, Jongdae (Frontiers in Immunology, 2021)
Although cancers arise from genetic mutations enabling cells to proliferate uncontrollably, they cannot 24 thrive without failure of the anticancer immunity due in a large part to the tumor environment’s 25 influence on effector and regulatory T cells. The field of immune checkpoint inhibitor (ICI) therapy 26 for cancer was born out of the fact that tumor environments paralyze the immune cells that are supposed 27 to clear them by activating the immune checkpoint molecules such as PD-1. While various subsets of 28 effector T cells work collaboratively to eliminate cancers, Tregs enriched in the tumor environment 29 can suppress not only the native anticancer immunity but also diminish the efficacy of ICI therapies. 30 Because of their essential role in suppressing autoimmunity, various attempts to specifically deplete 31 tumor-associated Tregs are currently underway to boost the efficacy of ICI therapies without causing 32 systemic autoimmune responses. A better understanding the roles of Tregs in the anti-cancer immunity 33 and ICI therapies should provide more specific targets to deplete intratumoral Tregs. Here, we review 34 the current understanding on how Tregs inhibit the anti-cancer immunity and ICI therapies as well as 35 the advances in the targeted depletion of intratumoral Tregs.